(untitled) (Transport systems and technologies, 2021)
Modern vehicles operated on the railways of Ukraine have almost exhausted or exceeded their resource. The overuse of financial and material resources for their maintenance continues. The standard service life of vehicles was calculated on stable economic conditions of use of vehicles and their timely updating in process of aging. The service life of modern vehicles is determined by the influence of many factors, the disregard of which can lead to significant costs, even in compliance with the standard service life. For railway transport, these factors need modern clarification, as in operation their service life often exceeds the standard or, as for intermodal transport, the service life does not have a strict justification. Accordingly, the article analyzes the issues of assessing the impact on the service life of vehicles of the components of the cost of its maintenance and average daily mileage. It is shown that, firstly, the definition of the service life of vehicles must be linked to the cost of vehicle development, its creation, testing and production, the cost of operation and storage, as well as additional costs, and secondly , with the optimal average daily mileage, at which all the costs are minimal.